2004
DOI: 10.1523/jneurosci.2860-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Degrading Enzyme as a Downstream Target of Insulin Receptor Signaling Cascade: Implications for Alzheimer's Disease Intervention

Abstract: Insulin-degrading enzyme (IDE) is one of the proteins that has been demonstrated to play a key role in degrading ␤-amyloid (A␤) monomer in vitro and in vivo, raising the possibility of upregulating IDE as an approach to reduce A␤. Little is known, however, about the cellular and molecular regulation of IDE protein. Because one of the main functions of IDE is to degrade insulin, we hypothesized that there is a negative feedback mechanism whereby stimulation of insulin receptor-mediated signaling upregulates IDE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
196
3
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(211 citation statements)
references
References 39 publications
10
196
3
2
Order By: Relevance
“…Hence current diabetes therapeutic(s) may have value in treating Alzheimer's disease. Potential molecular connections include abnormal expression/ activity of insulin-degrading enzyme [7,8], glycogen synthase kinase-3 (GSK3) [9,10], cholesterol biosynthesis enzymes [11] and activated glycation end-products [12,13], and cerebrovascular alterations [14]. However the major clinical commonality in epidemiological studies is hyperinsulinaemia (indicative of insulin resistance).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Hence current diabetes therapeutic(s) may have value in treating Alzheimer's disease. Potential molecular connections include abnormal expression/ activity of insulin-degrading enzyme [7,8], glycogen synthase kinase-3 (GSK3) [9,10], cholesterol biosynthesis enzymes [11] and activated glycation end-products [12,13], and cerebrovascular alterations [14]. However the major clinical commonality in epidemiological studies is hyperinsulinaemia (indicative of insulin resistance).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…195 Insulin signalling was also shown to modulate IDE levels in vitro, in a transgenic mouse model and in human AD brain samples. 196 As such, enhancing the efficacy of insulin signalling in the brain may in turn increase IDE levels and improve Ab degradation. In addition, this insulin signalling and IDE deficiencies that characterize AD may be incorporated into diagnostic tests, as discussed in a later section.…”
Section: Ab-degrading Enzymesmentioning
confidence: 99%
“…It is possible that the deficit in IDE activity at a high glucose concentration may lead to a compensatory increase in IDE expression. A study carried out in primary hippocampal neuron culture suggested that insulin may induce the increase in IDE protein level through the phosphatidylinositol-3 kinase pathway; however, the glucose concentration in the culture medium was not stated [30].…”
Section: Discussionmentioning
confidence: 99%